First-principles study of magnetism in some novel MXene materials. Issue 72 (16th December 2020) - Luo, Kan; Zha, Xian-Hu; Huang, Qing; Lin, Cheng-Te; Yang, Minghui; Zhou, Shenghu; Du, Shiyu
Abstract : Magnetic two-dimensional materials have gained considerable attention due to their special topologies and promising applications in electronic and spintronic devices, and the critical temperature could be evaluated through Monte Carlo simulations. Abstract : Magnetic two-dimensional materials have gained considerable attention in recent years due to their special topologies and promising applications in electronic and spintronic devices. As a new family of two-dimensional materials, MXene materials may have unusual magnetic properties. In this work, the structural stabilities and electronic properties of 1H and 1T type pristine M2 C (M = Sc, Ti, Fe, Co, Ni, Cu, Zn) MXenes with different magnetic configurations were calculated and compared. The critical temperatures of the magnetic MXenes were evaluated through Monte Carlo simulations using the spin–exchange coupling parameters. The results suggest that the ground-state 1T-Ti2 C and 1T-Fe2 C, 1H-Co2 C MXenes are antiferromagnetic or ferromagnetic materials with high Néel or Curie temperatures. Different from the other pristine M2 C MXenes with metallic properties, indirect band gaps were found for the 1T-Ti2 C and 1T-Ni2 C MXenes, which may be useful for their application in information storage or sensors. The findings are expected to promote the development of novel devices based on MXenes and their magnetic properties.